Leadership of elite coaches: The relationship among philosophy, practice, and effectiveness criteria - Rui Gomes, A.; Araújo, V.; Resende, R.; Ramalho, V. (International Journal of Sports Science & Coaching, 2018)
Coaching philosophy is an important topic in both coaching literature and education. However, there is little research regarding the way that coaches` philosophies translate into their practices. Additionally, there is very little information about the specific effectiveness criteria coaches use to evaluate their philosophies and practice. This study addresses the complex set of relationships among coaches` philosophies, perceptions of their practice, and effectiveness criteria. Ten elite coaches were selected for the study (nine males; one female), all of whom had successful careers in their respective sports. The coaches responded to an interview guide that addressed the topics of philosophy, practice, and effectiveness criteria. Deductive and inductive data analysis procedures were used to organize the collected information. The results indicated four main themes: (a) the importance of athlete motivation, (b) the importance of building a relationship with athletes based on personal respect, (c) the presence of high levels of cohesion among the team, and (d) the need for formal and informal rules that regulate the team`s functioning. There were several areas in which coaches did not establish a relationship linking philosophy, practice, and effectiveness criteria. The results suggest the need to educate coaches regarding methods of establishing a relationship among their philosophies, their practices, and the effectiveness criteria they use to evaluate their performance as coaches.